Una propuesta de marketing para un archivo institucional - Batista dos Santos, Vanderlei (2012)
El presente trabajo analiza la enseñanza de la archivología tradicional, y su direccionalidad al manejo y uso de los acervos históricos, haciendo que la institución valorice poco la acción del archivista en las demás fases del ciclo de  vida del documento. En consecuencia, propone un programa de marketing, direccionado específicamente a la promoción, mostrando los beneficios del uso de la información archivística en la práctica administrativa y en la toma de decisiones. -- This work analyzes the traditional archival practices and proposes innovations  about this topic. The traditional archivist education and training process  underlines  the treatment and use of the historical documents. In this  address,  the Institution do not pay attention to the archivist working process developed  during the other phases of the life cycle of historical documents. For this  reason, this work proposes a program of marketing, focusing mainly on  promotional issues. Stressing  on the benefits of using the historical archive information, this work is very useful to improve administrative practices such as planning and  taking  decisions.